2015
DOI: 10.1186/s13063-015-1040-3
|View full text |Cite
|
Sign up to set email alerts
|

The ROAM/EORTC-1308 trial: Radiation versus Observation following surgical resection of Atypical Meningioma: study protocol for a randomised controlled trial

Abstract: BackgroundAtypical meningiomas are an intermediate grade brain tumour with a recurrence rate of 39–58 %. It is not known whether early adjuvant radiotherapy reduces the risk of tumour recurrence and whether the potential side-effects are justified. An alternative management strategy is to perform active monitoring with magnetic resonance imaging (MRI) and to treat at recurrence. There are no randomised controlled trials comparing these two approaches.Methods/DesignA total of 190 patients will be recruited from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
109
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(112 citation statements)
references
References 17 publications
0
109
1
2
Order By: Relevance
“…26 This will be tested in the future with NRG Oncology protocol BN-003 and the ongoing Radiation versus Observation following surgical resection of Atypical Meningioma (ROAM)/European Organization for Research and Treatment of Cancer (EORTC)-1308 trial, for which, based on the results of the current study, we would support patient enrollment for the evaluation of disease-free-survival. 27 Although studies to date have demonstrated improvement in disease control with RT, the results of the current study (which we believe to have enough patients and follow-up) actually suggested that this improved control is likely to lead to improved survival in the future. On multivariate analysis, the current study data also demonstrated poorer survival in African American patients.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…26 This will be tested in the future with NRG Oncology protocol BN-003 and the ongoing Radiation versus Observation following surgical resection of Atypical Meningioma (ROAM)/European Organization for Research and Treatment of Cancer (EORTC)-1308 trial, for which, based on the results of the current study, we would support patient enrollment for the evaluation of disease-free-survival. 27 Although studies to date have demonstrated improvement in disease control with RT, the results of the current study (which we believe to have enough patients and follow-up) actually suggested that this improved control is likely to lead to improved survival in the future. On multivariate analysis, the current study data also demonstrated poorer survival in African American patients.…”
Section: Discussionmentioning
confidence: 57%
“…The preliminary results (in abstract form) of the phase 2 NRG/Radiation Therapy Oncology Group (RTOG) 0539 study found that a combination of surgery/RT led to significantly improved progression‐free survival in a group of patients treated for recurrent grade 1 lesions and completely resected atypical lesions . This will be tested in the future with NRG Oncology protocol BN‐003 and the ongoing Radiation versus Observation following surgical resection of Atypical Meningioma (ROAM)/European Organization for Research and Treatment of Cancer (EORTC)‐1308 trial, for which, based on the results of the current study, we would support patient enrollment for the evaluation of disease‐free‐survival . Although studies to date have demonstrated improvement in disease control with RT, the results of the current study (which we believe to have enough patients and follow‐up) actually suggested that this improved control is likely to lead to improved survival in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These homogenous subgroups may help predict clinical course, thus allowing for customized follow-up planning to manage resource intense investigations such serial imaging while optimizing patient care. Our results could also help guide recruitment protocols for future and ongoing clinical trials, which are currently limited by the uncertainty of clinical outcomes in atypical meningiomas 24 . The approach in this study lend to the utility of complex molecular signatures in augmenting histological diagnosis and resolving other heterogeneous and challenging diseases.…”
Section: Discussionmentioning
confidence: 95%
“…Thirdly, the use of a competing risk analysis is appropriate in meningioma when there is a high risk that the event of interest (meningioma recurrence or meningioma-related death) will not be observed due to the high prevalence of over events, that is, death due to other causes. Indeed, this is the rationale behind current phase III atypical meningioma trials excluding patients with co-existing solid cancers [5] since the event of interest is recurrence.…”
mentioning
confidence: 99%